Aminated ZIF-8 to facilitate CO2 sieving through polyvinyl alcohol/ionic liquid membranes - Hong C.-H.; Leo C.P.; Ahmad N.N.R.; Ahmad A.L. (John Wiley and Sons Inc, 2025)
CO2 separation technology at low pressure is most desirable in carbon capture projects to mitigate global warming. Facilitated transport membranes offer selective and effective CO2 permeation using a wide range of carbon carriers at low pressure. Porous fillers were recently included as they can carry abundant fixed carriers besides offering open channels for CO2 permeation. This study investigates the effects of amine-modified zeolitic imidazolate framework-8 (ZIF-8) with well-defined micropores and gas sieving ability in polyvinyl alcohol (PVA) membranes containing an ionic liquid that worked as mobile carriers. The effects of amine-modified ZIF-8 and silica nanoparticles on membrane properties and separation performance were also compared. Fourier transform infrared spectra confirmed the incorporation of ZIF-8, secondary amine, IL anions, and silica nanoparticles in PVA membranes. Energy dispersive analysis showed the good dispersion of inorganic fillers. The amine-modified silica nanoparticles resulted in higher thermal stability compared to the amine-modified ZIF-8 in PVA membranes containing [bmin][Ac] ionic liquid, as shown in the thermogravimetric analysis. However, the CO2 separation performance of PVA membranes containing [bmim][Ac] ionic liquid was improved more significantly by the amine-modified ZIF-8 with microporous structure. A CO2/N2 ideal selectivity of 85.65 and CO2 permeance up to 4,502.91 GPU were attained. Unlike the CO2/N2 ideal selectivity, the CO2 permeance was not significantly affected either using [bmin][Ac] or [bmin][BF4]. The humid gas greatly enhanced the CO2 permeance without much changes in the CO2/N2 ideal selectivity due to the promotion of facilitated transport. ? 2024 Society of Chemical Industry and John Wiley & Sons, Ltd. ? 2024 Society of Chemical Industry and John Wiley & Sons, Ltd.